Nanocurcumin Protective Effect on Lipid Peroxide of Lead Acetate Induced White Rats (Rattus norvegicus) Ovarian Granulosa Cells - Anis Satus Syarifah1,2, Sri Agus Sudjarwo3 , Hendy Hendarto4 , Reny I’tishom5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: This study aims to investigate the protective effect of nanocurcumin on lipid peroxidation of ratovarian granulosa cells induced by lead acetate (Pb).Methods : A total of 45 mice were divided into a negative control group (C-) receiving corn oil, a positivecontrol group (C+) receiving corn oil and lead acetate (Pb) 40 mg/kg bw/day, experimental group 1 (E1),experimental group 2 (E2), experimental group 3 (E3) receiving 50, 100 and 200 mg/kg/day nanocurcumindissolved in corn oil and lead acetate (Pb) 40 mg/kg bw/day. The treatment was given orally and the treatmenttime was daily at 08.00 AM for 26 days. Ovaries were removed for immunohistochemical analysis of MDAexpression.Result : The positive control group had the highest MDA expression of ovarian granulosa cells (94.2 ± 10.5)and was significantly different (p <0.05) from negative control group (1.5 ± 1.4), experimental group 1 (17.4± 10.5), experimental group 2 (11.4 ± 8.5) and experimental group 3 (7.2 ± 4.0).Conclusion : Nanocurcumin as a protective oxidative stress on ovarian granulosa cells due to exposure tolead acetate, by protecting lipid peroxidation.